Anticonvulsants for Psychiatric Disorders in Children and Adolescents: A Systematic Review of Their Efficacy - Davico, Chiara; Canavese, Carlotta; Vittorini, Roberta; Gandione, Marina; Vitiello, Benedetto (Frontiers in Psychiatry, 2018)
Aim: Anticonvulsant medications are frequently used in clinical practice to treat psychiatric disorders in children and adolescents, but the evidence for their efficacy is uncertain. We conducted a systematic review of published randomized controlled trials (RCT) that assessed the psychiatric benefit of anticonvulsants in patients under 18 years of age. Method: The Medline, Scopus, Web of Science, and ClinicalTrials.gov databases were systematically searched for peer-reviewed primary publications of RCTs with a minimum of 10 patients per treatment arm through December 2017. Results: Out of 355 identified non-duplicative publications, 24 met the inclusion criteria. Most RCTs were to treat bipolar disorder (n=12) or manage recurrent aggression (n=9). Few (n=3) had both multisite design and adequate statistical power. Valproate was the most frequently studied anticonvulsant (n=15). Out of three placebo-controlled RCTs of valproate in bipolar disorder, none showed efficacy. In 4 RCTs, valproate was inferior to the antipsychotic risperidone. In six small, single-site RCTs, anticonvulsant was better than placebo in controlling recurrent aggression. Conclusions: Currently available RCTs do not support the efficacy of anticonvulsants as mood stabilizers in children. There is some preliminary evidence from small RCTs of efficacy in the control of aggression and behavioral dyscontrol in conduct disorder, autism, and intellectual disability.